A exigência de uma nova justiça social: uma análise de Uma teoria de justiça de Rawls a partir de duas vias da filosofia ocidental - Agbe, Fafadzi Akpene (2018)
The main objective of this work is to study the conception of justice as fairness according to John Rawls in his work "The Theory of Justice". The analytical and continental aspects of contemporary Western philosophy in the philosopher's thinking show that it is precisely the defeated challenge of putting into dialogue both traditions that explain the impact of the work, in a way that will makes it possible to return some of the substantive issues in political theory. Thus the main result in this respect is the demand for social justice in the basic structures of societies concerned with the fate of the less fortunate. The principle of difference is the driving force of this demand